2019
DOI: 10.1016/j.humpath.2018.11.033
|View full text |Cite
|
Sign up to set email alerts
|

FAM134B promotes esophageal squamous cell carcinoma in vitro and its correlations with clinicopathologic features

Abstract: Family with sequence similarity 134, member B (FAM134B) is an autophagy regulator of endoplasmic reticulum first discovered to be involved in the pathogenesis of esophageal squamous cell carcinoma (ESCC). The present study examined the functional behavior of FAM134B in cancer cells and the association of FAM134B expression with clinicopathologic factors in patients with ESCC. Expression at both the mRNA and protein levels was investigated using real-time polymerase chain reaction and immunohistochemistry. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…In addition, higher expressions of EPAS1 protein in mutated samples indicate tumour-supporting roles of EPAS1 in the pathogenesis of phaeochromocytoma/paraganglioma. Previous studies reported that dysregulation and gain-of-function mutation of EPAS1 associated with neuroendocrine tumours such as paraganglioma and phaeochromocytomas by inducing pseudo-hypoxic tumour microenvironment [9,13,39]. Thus, the findings of the current study agree with previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, higher expressions of EPAS1 protein in mutated samples indicate tumour-supporting roles of EPAS1 in the pathogenesis of phaeochromocytoma/paraganglioma. Previous studies reported that dysregulation and gain-of-function mutation of EPAS1 associated with neuroendocrine tumours such as paraganglioma and phaeochromocytomas by inducing pseudo-hypoxic tumour microenvironment [9,13,39]. Thus, the findings of the current study agree with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have demonstrated that mutations in endothelial PAS domain-containing protein 1 (EPAS1) is associated with manifestations of phaeochromocytomas and paragangliomas [1,9,[12][13][14]. EPAS1, also known as HIF-2α, encodes for one of the hypoxia inducible factor (HIF) family members, which is involved in the hypoxic response [15].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of caspases -3, -8, -9 in SW480 and SW48 followed by treated with KRL in cells pretreated with respective inhibitors in and SW480 cell lines were significantly inhibited by KRL. The inhibitory effects were higher than that of the pea lectin [16].…”
Section: Krl Induced Activation Mitochondrial Intrinsic Apoptotic Patmentioning
confidence: 65%
“…Five ESCC cancer cell lines (KYSE70, KYSE150, KYSE450, KYSE520, and HKESC-1) and one nonneoplastic keratinocyte (HaCaT) were used in the present study. All the cells were maintained as previously described (26,27).…”
Section: Cell Culturementioning
confidence: 99%
“…Subsequently, the clones were stained with crystal violet (0.5%) for 2 h at room temperature and washed with tap water. Finally, after being air-dried, images of the plates were taken, and clone formation rates were calculated as previously described (26).…”
Section: Colony Formation Assaymentioning
confidence: 99%